Pengungkapan Corporate Social Responsibility Sebagai Bentuk Komunikasi Citra Perusahaan - Ni Putu Ari Aryawati; I Ketut Putu Suardana (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2021)
The aim of this study to examine the influence of corporate social responsibility disclosure as a legitimation of firm image at go public firm. Based on legitimacy theory, there is a possible corporate social responsibility disclosure as a maintain corporate image to community. The sample of this research is manufacturing company which are listed in Indonesia Stock Exchange (IDX) in 2018 – 2020. The result of this research shows that more detail and higher disclosure corporate social responsibility, the higher of corporate image. This result provides legistimation theory for support the environmental firm.